2021
DOI: 10.7759/cureus.13837
|View full text |Cite
|
Sign up to set email alerts
|

Increased Isolation of Extended-Spectrum Beta-Lactamase-Producing Escherichia coli From Community-Onset Urinary Tract Infection Cases in Uttarakhand, India

Abstract: Background: Management of community-acquired urinary tract infection (CA-UTI) relies heavily on empirical antibiotic therapy. Knowledge of the proportion of drug-resistant isolates especially extended-spectrum beta-lactamase (ESBL)-producing Escherichia coli ( E. coli ), and various risk factors for acquisition are essential. Method: Outpatient-treated CA-UTI cases were enrolled (continuously for three months), and microbiological analysis of urine sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 14 publications
(14 reference statements)
1
11
0
Order By: Relevance
“…This observation questions the use of fluoroquinolone as the empiric treatment. [ 22 ] This is consistent with earlier studies. [ 5 ] Therefore, nitrofurantoin and fosfomycin may be used as the empirical drug of choice in the study area as a potential treatment of UTI.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This observation questions the use of fluoroquinolone as the empiric treatment. [ 22 ] This is consistent with earlier studies. [ 5 ] Therefore, nitrofurantoin and fosfomycin may be used as the empirical drug of choice in the study area as a potential treatment of UTI.…”
Section: Discussionsupporting
confidence: 94%
“…These findings were similar to many studies abroad but dissimilar to a study from Kerala. [ 21 22 ] However, Gram-negative isolates were sensitive to carbapenems and antipseudomonal penicillins, these drugs cannot be recommended in outpatient settings due to their supervised drug administration protocols. Fosfomycin and nitrofurantoin have shown intermediate to full susceptibility pattern (68.8% and 71.9% respectively).…”
Section: Discussionmentioning
confidence: 99%
“…32 However, the prevalence of ESBL producers in our study was comparatively less than previous studies reported by Bajpai et al 33 (36.8%), Taneja et al 34 (40.2%), Gautam et al . 35 (33%) and Kumar et al 36 (46.6%) from different parts of India. This increased prevalence of ESBL-producing E. coli isolates is a serious peril for healthcare as these organisms can cause many severe infections in humans even in countries with advanced public health and healthcare facilities.…”
Section: Discussionmentioning
confidence: 93%
“…This was quite similar as observed through a research work by N. Kumar et al where the presence of ESBL producers was 46.6% in uropathogens. 18 These two organisms have been common pathogens for both community-acquired hospital-acquired (HA). The multidrug resistance (MDR) of ESBL-producing isolates has been a matter of concern.…”
Section: Discussionmentioning
confidence: 99%